Association of dairy product consumption with metabolic and inflammatory biomarkers in adolescents: a cross-Sectional Analysis from the LabMed study - Abreu, Sandra (2019)
This study aimed to investigate the association between dairy product consumption and metabolic and inflammatory biomarkers in Portuguese adolescents, and whether the association differed by weight status. A cross-sectional study was conducted during the school year 2011/2012 with 412 Portuguese adolescents (52.4% girls) in 7th and 10th grade (aged 12 to 18 years old). The World Health Organization cutoffs were used to categorize adolescents as non-overweight (NW) or overweight (OW). Blood samples were collected to analyze C-reactive protein (CRP), interleukin-6 (IL-6), leptin, and adiponectin. Dairy product intake was evaluated using a food frequency questionnaire. Participants were divided by tertiles according to the amount of dairy product consumed. The associations between dairy product consumption with metabolic and inflammatory biomarkers were evaluated using generalized linear regression models with logarithmic link and gamma distribution and adjusted for potential confounders. The majority of adolescents were NW (67.2%). NW adolescents had lower IL-6, CRP, and leptin concentration than their counterparts (p < 0.05, for all comparisons). Higher levels of total dairy product and milk intake were inversely associated with IL-6 (P for trend <0.05, for all) in NW adolescents, but not in OW adolescents. NW adolescents in the second tertile of yogurt consumption had lower level of IL-6 compared to those in the first tertile (p = 0.004). Our results suggest an inverse association between total dairy product and milk intake and serum concentrations of IL-6 only among NW adolescents.